Disruption of the methyltransferase-like 23 gene METTL23 causes mild autosomal recessive intellectual disability. (13th March 2014) - Bernkopf, Marie; Webersinke, Gerald; Tongsook, Chanakan; Koyani, Chintan N.; Rafiq, Muhammad A.; Ayaz, Muhammad; Müller, Doris; Enzinger, Christian; Aslam, Muhammad; Naeem, Farooq; Schmidt, Kurt; Gruber, Karl; et al.
Abstract : We describe the characterization of a gene for mild nonsyndromic autosomal recessive intellectual disability (ID) in two unrelated families, one from Austria, the other from Pakistan. Genome-wide single nucleotide polymorphism microarray analysis enabled us to define a region of homozygosity by descent on chromosome 17q25. Whole-exome sequencing and analysis of this region in an affected individual from the Austrian family identified a 5 bp frameshifting deletion in the METTL23 gene. By means of Sanger sequencing of METTL23, a nonsense mutation was detected in a consanguineous ID family from Pakistan for which homozygosity-by-descent mapping had identified a region on 17q25. Both changes lead to truncation of the putative METTL23 protein, which disrupts the predicted catalytic domain and alters the cellular localization. 3D-modelling of the protein indicates that METTL23 is strongly predicted to function as an S -adenosyl-methionine (SAM)-dependent methyltransferase. Expression analysis of METTL23 indicated a strong association with heat shock proteins, which suggests that these may act as a putative substrate for methylation by METTL23. A number of methyltransferases have been described recently in association with ID. Disruption of METTL23 presented here supports the importance of methylation processes for intact neuronal function and brain development.